PERAN GREENPEACE DALAM MENANGANI KEBAKARAN HUTAN DAN LAHAN DI PROVINSI RIAU TAHUN 2015 - Delvi Tri Amanda; Hendrini Renolafitri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study describes the role of Greenpeace in dealing with forest and land fires that occurred in Riau province in 2015. Forest and land fires that occurred in Riau Province are the worst areas in the Sumatra Region. The causes of the forest and land fires that occurred in Riau Province were mostly caused by human activities. The fires that occurred that year caused the people of Riau Province to feel the impact in the form of air pollution, namely smog, so that Greenpeace which is engaged in environmental NGOs (Non-Governmental Organizations) has a role in dealing with forest and land fire problems that occurred in Riau Province in 2015. The author collects data from interviews, books, academic journals, and internet sources related to research issues regarding Greenpeace's role in dealing with forest and land fires in Riau Province. The writer uses the Greenthought perspective and the level of group analysis. While the theory used in this theory is the theory of the Role of NGOs (Non-Govermental Organizations). The results of the study show that Greenpeace's role in dealing with land forest fires that occurred in Riau Province was the first in the field of implementation. Greenpeace formed a Fire Prevention Team which is a form of Forest Action Without Fire. The Fire Prevention Team conducted Monitoring, Investigation and extinguishing fires in burning forests in Riau in 2015. Second, in the field of catalysts, Greenpeace provides briefing to the public through social media and directly in the form of workshops. Third, in the field of Greenpeace partners in carrying out their actions in collaboration with the Karhutla disaster task force (SATGAS), which consists of the National Police and the TNI and Greenpeace in carrying out their campaigns. Keywords: Role, NGO (Non Govermental Organization), Forest and Land Fires, Greenpeace, Campaign.